2013
DOI: 10.1016/j.micres.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the genetic similarities of fingerprints from Escherichia coli O157:H7 isolated from different sources in the North West Province, South Africa using ISR, BOXAIR and REP-PCR analysis

Abstract: The aim of this study was to determine the genetic relationships of Escherichia coli O157:H7 isolated from pigs, cattle, pork, beef, humans and water samples using REP, ISR and BOXAIR PCR analysis. A total of 94 isolates were subjected to the REP-PCR analysis while 95 were screened for ISR and BOXAIR PCR fingerprints. The band sizes for amplicons from the ISR-PCR analysis ranged from 0.173kb to 0.878kb. However, a large proportion of the isolates had four bands ranging from 0.447kb to 0.878kb. Cluster analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Based on the results of the present study, some isolates from different sources/samples may have originated from a single source and been transmitted through different routes to vegetables or from diverse sources, as shown by similar and differing banding patterns. Our results are in agreement with previous studies reporting the similarity of fingerprints strains of E. coli O157:H7 obtained from different sources.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the results of the present study, some isolates from different sources/samples may have originated from a single source and been transmitted through different routes to vegetables or from diverse sources, as shown by similar and differing banding patterns. Our results are in agreement with previous studies reporting the similarity of fingerprints strains of E. coli O157:H7 obtained from different sources.…”
Section: Discussionsupporting
confidence: 93%
“…DNA fingerprints were analyzed with the BioNumerics software version 4 (Applied Maths NV, Sint-Martens-Latem, Belgium) as described elsewhere [34, 35, 45, 46]. The similarity-analysis of the results of each genotyping assay was calculated using Dice coefficient; cluster analysis of the similarity matrices was generated using Unweighted Pair Group Method with Arithmetic Mean (UPGMA) algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…Some selected E. coli strains were investigated genetically with the use of ERIC-PCR. Osińska et al [59] reported ERIC-PCR genomic ngerprinting technique as a vital tool for evaluating genetic relationships between bacterial strains isolated from environmental niches and some other studies reported ERIC-PCR genotypic diversity of multidrug resistant (MDR) bacterial strains isolated from different sources [60,61], However, in this study we analyzed selected E. coli strains comprising some CREC with the use of ERIC-ngerprinting in order to evaluate the links that exist between strains isolated from different sources. ERIC-PCR has been demonstrated to be an effective method in determining the genetic diversity or relatedness among bacterial species by grouping clusters according to band sizes [62].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 243 different environmental samples ranging from surface water (47), WWTPs nal e uents (29), hospital e uents (27) to irrigation water (45), soil (60) and vegetables (35) were collected from January to September 2018. Water samples (1.5L) was collected in duplicate using sterile glass bottles and transported in an ice box to the research laboratory for bacteriological analyses within 6 hours of sampling.…”
Section: Sample Collectionmentioning
confidence: 99%